2018
DOI: 10.1007/s00280-018-3588-6
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase 2 study of gemcitabine and cisplatin with or without vitamin supplementation in patients with advanced esophagogastric cancer

Abstract: PurposePreclinical research and prior clinical observations demonstrated reduced toxicity and suggested enhanced efficacy of cisplatin due to folic acid and vitamin B12 suppletion. In this randomized phase 2 trial, we evaluated the addition of folic acid and vitamin B12 to first-line palliative cisplatin and gemcitabine in patients with advanced esophagogastric cancer (AEGC).MethodsPatients with AEGC were randomized to gemcitabine 1250 mg/m2 (i.v. days 1, 8) and cisplatin 80 mg/m2 (i.v. day 1) q 3 weeks with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Included studies examined Vitamin B1 ( n = 1), 17 Vitamin B3 ( n = 2), 17,18 Vitamin B6 ( n = 16), 1732 Vitamin B9 ( n = 15), 1723,28,3036 Vitamin B12 ( n = 16), 1723,28,3033,35,36 and Vitamin B Complex ( n = 1). 37 Details of the included studies and results can be found in Tables 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Included studies examined Vitamin B1 ( n = 1), 17 Vitamin B3 ( n = 2), 17,18 Vitamin B6 ( n = 16), 1732 Vitamin B9 ( n = 15), 1723,28,3036 Vitamin B12 ( n = 16), 1723,28,3033,35,36 and Vitamin B Complex ( n = 1). 37 Details of the included studies and results can be found in Tables 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
“…The findings are as follows B9 and B12 showed a higher risk of colorectal cancer HR: 1.77; 95% CI, 1.08–2.90 p = 0.02, as well as a higher risk of overall cancer HR: 1.25; 95% CI, 1.00–1.53 p = 0.05. 33 Van Zweeden et al, 35 studied the combination effect of both B9 and B12 on advanced esophagogastric cancer (AEGC) concluding that combined B9 and B12 had no effect on OS or TTP ( p = 0.9). Singer et al 20 found that maternal intake of one-carbon metabolism nutrients from food or supplements correlated to a lower occurrence of childhood acute lymphoblastic leukemia (OR for one-unit change in the principal component = 0.91, CI: 0.84–0.99).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although treatment options are limited for patients with unresectable, locally advanced, or metastatic esophageal cancer, a portion of patients could benefit from the comprehensive treatment of chemotherapy, targeted therapy and immunotherapy with immune checkpoint inhibitors ( Eltweri et al, 2019 ; Kojima et al, 2020 ; Lopez et al, 2020 ; Stroes et al, 2020 ). The commonly used chemotherapeutic agents in clinics include platinum drugs, 5-fluorouracil (5-FU), adriamycin (ADM), paclitaxel (PTX), irinotecan, gemcitabine (GEM), and vinorelbine ( Liu S. L. et al, 2015 ; Wang Y. S. et al, 2016 ; Tin et al, 2018 ; van Zweeden et al, 2018 ; Ni et al, 2020 ). Molecular targeted therapy drugs include anti-HER2 monoclonal antibodies (trastuzumab and pertuzumab), oral tyrosine kinase inhibitors (TKIs) targeting HER-1/HER-2 (lapatinib), anti-vascular endothelial growth factor receptor 2 (VEGFR-2) antibody (ramucirumab) and anti-EGFR monoclonal antibody (panitumumab) ( Press et al, 2017 ; Shepard et al, 2017 ; Chakrabarti et al, 2018 ; Guo et al, 2018 ; Yamaguchi et al, 2018 ; De Vita et al, 2019 ; Hassan et al, 2019 ; Rogers et al, 2019 ; Wagner et al, 2019 ; Stroes et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, с 2010 года начали появляться результаты применения гемцитабина (от 1000 мг/м 2 до 1250 мг/м 2 ) в различных комбинациях при РП. При этом было получено улучшение общей выживаемости [3,18] Следует отметить, что до начала лечения в основной группе у 30 (85,7%) и в контрольной группе у 29 (82,8%) больных имелась дисфагия различной степени выраженности. При дисфагии III-IV степени в основной группе у 16 (45,7%) и в контрольной группе у 14 (40%) больных проводилось парентеральное питание, состав и объем которого зависел от состояния больного и лабораторных показателей.…”
Section: Introductionunclassified